Relationship between Macrovascular and Microvascular Hemodynamics Assessed by Spectrophotometry in Periodontal Diseases. (4th June 2021) - Figliuzzi, M. M.; Sestito, S.; Pacifico, D.; Parentela, L.; Rengo, Carlo
Abstract : Objective . The aim of this study is to identify a possible link between macrovascular hemodynamic status and microvascular hemodynamic indices in patients with periodontal disease. Methods and Materials . Seventeen adult patients are recruited on a voluntary basis at the Dentistry Department of the "Mater Domini" University of Catanzaro, with sampling that determines the lipid profile, blood glucose, inflammatory mediators, blood plasma viscosity: anamnesis, blood pressure measurement, and detection of anthropometric parameters: eco-Doppler of the carotid arteries and brachial arteries with noninvasive measurements of hemodynamics and evaluation of inflammation and periodontal circulation with a noninvasive spectroscopic technique. The subjects underwent a dental inspection with periodontal proves. The different indices of periodontal disease were evaluated. Results . The sites with high probing depth differ from the healthy ones, showing low oxygen saturation and a notable increase in tissue edema, but no correlation between macro- and microvascular values was found. Conclusion . Periodontal probing and spectroscopic examination showed the correlation between low oxygen saturation levels and tissue edema values with probing depth; however, no correlation between macrovascular hemodynamic status and microvascular hemodynamics indices was found probably given the heterogeneity of the population under consideration, the low number of data gathered, and the small sample size.